Keanekaragaman Lichenes di Kawasan Aliran Air Panas Jaboi Kecamatan Sukajaya Kota Sabang - Rahmah Nabila; Cut Ratna Dewi; Muslich Hidayat; Eriawati Eriawati; Mulyadi Mulyadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Biodiversity is a combination of the number of species and the number of individuals of each species in a community, one of which is in the Lichen group. Lichen is a form of mutualistic symbiosis between fungi and algae that morphologically and physiologically form a whole unit to produce new, unique individuals. This organism has an important role in the ecosystem, such as indicators of environmental quality, nutrient cycles, and soil surface cover. However, data on the diversity of Lichen species, especially in Geothermal areas, is still very limited so that information on their distribution and composition in the area is not optimal. This study aims to analyze the diversity index of Lichen species in the Jaboi Hot Spring area, Sukajaya District, Sabang City. The study was conducted in June 2025 using a combination of exploratory survey methods to determine research stations and transect line boundaries, as well as purposive sampling methods for Lichen sampling. Data were analyzed using the Shannon-Wiener diversity index (Ĥ). The results showed that there were 17 Lichen species belonging to 11 families with a total of 2027 colonies found in all observation stations. The obtained diversity index value was Ĥ = 2.819214, which is recommended as moderate diversity. These findings indicate that although the Jaboi Hot Springs area has unique environmental conditions due to geothermal activity, it still supports a diverse range of lichen species. This information is expected to form the basis for further research on lichen ecology, biodiversity conservation, and its potential use in geothermal areas. Furthermore, the results of this study can make important contributions to environmental management and bioindicator-based ecosystem quality monitoring.